กระบวนการคัดเลือกพิธีกรและผู้ประกาศข่าวของสถานีโทรทัศน์กองทัพบกช่อง 7 - เหมือนฝัน ประสานพานิช (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This research aims to study masters of ceremonies and announcers selection process of Masters of Ceremonies and Announcers Project produced by Channel 7 and to realize factors having effects on the selection process. According to the research it is found that selection process of masters of ceremonies and announcers can be divided into five steps that are 1) Planning and setting project’s policy 2) Application and the first selection 3) Training the selected applicants of the first selection 4) Testing as the final selection and 5) Interviewing in English. Three most major factors of applicants quality in the first selection process of Channel 7’s Masters and Ceremonies and Announcers Project are 1) Clear and fresh voice with correct pronunciation in proper speed 2) Good appearance with graceful personality and good taste in clothes 3) Reliability Another factor is strong health and self-confidence Five most major factors of applicants quality in the final selection are 1) Clear and fresh voice with correct pronunciation in proper speed 2) Good appearance with graceful personality and good taste in clothes 3) Reliability 4) Good communication skill with the ability to use appropriate words and 5) Capability of making audiences get the message. Another factor is self-confidence and wisdom to be able to handle any unexpected problems Apart from factors of applicants quality there are other factors in the selection process. The most important factor is policy of the owner and produce of the television station. The marketing system and the television station’s technology are also involved.